The Influence of Effective Communication, Job Satisfaction and Quality of Nursing Work Life on Caring Behavior of Inpatient Nurses At Rsud Kemayoran Jakarta - Hany Ernita,; Abdul Aziz,; Nurminingsih, (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Nurses play a vital role in hospital inpatient units, providing the bulk of health services and having the longest patient contact. Yet, patients and families often complain about nurse performance. Strengthening effective communication, job satisfaction, and quality of nursing work life (Quality of Nursing Work Life, QNWL) is essential to improve it. This study examines the influence of effective communication, job satisfaction and quality of nursing work life on caring behavior of inpatient nurses at RSUD Kemayoran Jakarta. Using a non-experimental cross-sectional analytic design, logistic regression analyzed the influence of independent variables on caring behavior. Questionnaires assessed effective communication, job satisfaction, QNWL, and nurse caring behavior among a population and sample of 31 respondents. Analysis used SPSS version 24.0. Effective communication influenced caring behavior (p = 0.032 < 0.05; OR = 36.976), as did job satisfaction (p = 0.032; OR = 36.976). Poor ratings in either increased poor caring behavior risk 36.976-fold. QNWL showed no influence (p = 0.781 > 0.05). Together, these variables explained 77.6% of caring behavior variance; 22.4% stemmed from other factors. Effective communication and job satisfaction exerted the strongest influences on inpatient nurses' caring behavior at RSUD Kemayoran Jakarta.